(untitled) (Journal of Global Arts Studies, 2024)
Background: Nuo opera is born from the mother of Nuo culture in folk art. As one of the more common forms of folk theater in traditional Chinese rural society, it is accompanied by the Nuo festival. In people’s daily life, it mainly carries the cultural functions of driving away ghosts and epidemics, praying for blessings, and avoiding disasters. The author’s birthplace is an area where Dong Nuo opera is circulated. Objective: Since the Dong people have had only a spoken language but no written language since ancient times, and even after the state promulgated the Dong script in 1958, there have been few records related to Dong Nuo opera. This indicates that there is still considerable room to explore the origin, cultural connotation, and historical changes of Xinhuang Dong Nuo opera. “Dong Dong Tui” is a Dong opera performed in Tianjing Village, Gongxi Township, Xinhuang Dong Autonomous County, Hunan Province. It is not only part of traditional Chinese Nuo culture but also a continuation of Dong history and culture. Methods: This paper takes the Dong Nuo opera “Dong Dong Tui” and “Jumping Kid” as the research object, consulting a large amount of material and sorting out its body movements. Results: By taking “Jumping Kid” in the Dong Nuo opera “Dong Dong Tui” as the key research object, this paper attempts to explore this intangible cultural heritage from four aspects: the historical origin and circulation of Dong Nuo opera, the costumes, roles, and props of the little ghosts, the jumping method of “Jumping Kid,” and reflections on its inheritance and development. Conclusion: This study restores a complete section of the jumping method of “Jumping Kid” in “Dong Dong Tui” and, based on practical teaching experience, designs a lesson plan for Nuo opera appreciation classes in primary and secondary schools.